The evolution of the upper layer of light postagrogenic solonetz from caspian lowland by the amount of distributed minerals of different fractions - E. B. Varlamov; N. P. Chizhikova; M. P. Lebedeva; N. A. Churilin (Бюллетень Почвенного института им. В.В. Докучаева, 2017)
The morphologic, physical, mineralogic and chemical specificities of solonetzic process occurrence are studied in the arable layer from the non-meliorated solonetz for 50-year period of its post-agrogenic evolution. The mineralogic analysis of the separate grain fractions (10 mm) from microhorizons was conducted. Morphologically these grain fractions were specific for the crust horizon. It is revealed that the silty fraction of the soil forming clay loam is dominated by unordered complex mica-smectite formations, and in lesser concentrations there occur hydromicas, chlorites and caolinite. The former arable layer in the profile is characterized by the different correlation of the same mineral phases than in the other layers. The content of silty particles is dominated mostly by hydromicas. It is revealed that in all fractions